Principles for Digital Development (digitalprinciples.org, 2018)
The Principles for Digital Development serve as a compass for those working to promote sustainable and inclusive development in today’s complex digital landscape. Using these Principles as a starting point, policymakers, practitioners, and technologists will be better equipped to ensure that all people can benefit from digital initiatives and from the broader digital society. Originally developed in 2014, the Principles are officially endorsed by more than 300 organizations, including donors, international organizations, and civil society organizations. During the first decade (2014-2024), they widely influenced funder procurement policies and the design and implementation of development programs. In 2024, the Principles were updated in consultation with a diverse set of individuals and organizations. Through this effort, the community expressed the need for the Principles to better reflect that people today largely interact with technology outside of development programs. Today, all people – even those who do not yet have access to or use technology – live in societies that are increasingly shaped by digital ecosystems that can bring both immense benefit and immense harm. Therefore, the refreshed Principles recognize the need for radical inclusion and local ownership; elevate issues arising from the generation and use of digital data; and intentionally speak to the original audience while resonating further with the full diversity of individuals and organizations that exert power over the design, deployment, and governance of digital systems and solutions. The Principles are mutually reinforcing, as they emphasize the actions needed to ensure no one is left behind in an increasingly digital world.